Rhythm Control Versus Rate Control in Patients With Atrial Fibrillation and Heart Failure With Preserved Ejection Fraction: Insights From Get With The Guidelines—Heart Failure. Issue 24 (17th December 2019) - Kelly, Jacob P.; DeVore, Adam D.; Wu, JingJing; Hammill, Bradley G.; Sharma, Abhinav; Cooper, Lauren B.; Felker, G. Michael; Piccini, Jonathan P.; Allen, Larry A.; Heidenreich, Paul A.; Peterson, Eric D.; Yancy, Clyde W.; et al.
Abstract : Background: Limited data exist to guide treatment for patients with heart failure with preserved ejection fraction and atrial fibrillation, including the important decision regarding rate versus rhythm control. Methods and Results: We analyzed the Get With The Guidelines—Heart Failure (GWTG‐HF) registry linked to Medicare claims data from 2008 to 2014 to describe current treatments for rate versus rhythm control and subsequent outcomes in patients with heart failure with preserved ejection fraction and atrial fibrillation using inverse probability weighted analysis. Rhythm control was defined as use of an antiarrhythmic medication, cardioversion, or AF ablation or surgery. Rate control was defined as use of any combination of β‐blocker, calcium channel blocker, and digoxin without evidence of rhythm control. Among 15 682 fee‐for‐service Medicare patients, at the time of discharge, 1857 were treated with rhythm control and 13 825 with rate control, with minimal differences in baseline characteristics between groups. There was higher all‐cause death at 1 year in the rate control compared with the rhythm control group (37.5% and 30.8%, respectively, P <0.01). The lower 1‐year all‐cause death in the rhythm control group remained after risk adjustment (adjusted hazard ratio, 0.86; 95% CI, 0.75–0.98; P =0.02). Conclusions: Rhythm control in patients aged 65 and older with heart failure with preserved ejection fraction and AF was associated with a lower risk of 1 year all‐cause mortality. Future prospective randomized studies are needed to explore this potential benefit.